“TATAR” IN THE TURCO-MONGOL TRADITION OF THE LATER JOCHID HISTORICAL SOURCES - Nagamine H. (Золотоордынское обозрение)
This paper focuses on “Tatar Khan” (brother of Moghol Khan) inserted into the genealogy of Turco-Mongol tradition (history of the Turco-Mongol tribes) in Yazdī’s Ẓafar-nāma (Muqaddima). This paper is a modest attempt to provide new material on the question of how the genealogy of Tatar Khan was narrated in the Turco-Mongol tradition of the later Jochid sources, a question that has not received much attention so far. Research materials: Yazdī’s Ẓafar-nāma (Muqaddima) and historical sources written in the Later Jochid states: Oghuz (va) Alan Qoa va Shaybānī-nāma, Anonymous Shaybānī-nāma, Zubdat al-Āthār, Sharaf-nāma-yi Shāhī, Baḥr al-Asrār, Shajara-yi Turk, Es-seb‘ü’s-seyyâr, and ‘Umdet ül-Ahbār. Results and novelty of the research: In general, there is a tendency to gradually weaken and simplify the history of Tatar Khan and his descendants in the Later Jochid sources. This may be due to the importance of the genealogy of Moghol Khan’s descendants related to the Chinggisids/Jochids. Among these sources, the Shajara-yi Turk is characteristic; in it, the history of Tatar Khan and his descendants is adapted into a more ‘pro-Mongol’ one. On the other hand, the historiography of the Crimean Khanate, which identified itself as both ‘Mongols’ and ‘Tatars’, presented a stark contrast. There, the story of the branching and conflicting descendants of the brothers Tatar Khan and Moghol Khan is either not told (Es-seb‘ü’s-seyyâr) or it describes and emphasizes their unification (‘Umdet ül-Ahbār). Such different ways of narrating the genealogy of Tatar Khan could reflect the political and ethnic situation in which the Later Jochid states found themselves.